On Some Rhetorical-pedagogical Strategies in Epictetus’ Discourses Concerning Proairesis - Braicovich, Rodrigo Sebastián (2013)
The paper aims to clarify some features of Epictetus’ specific usage of the concept of proairesis throughout his Discourses. This will be done by suggesting that a number of problematic expressions concerning proairesis and its freedom should be understood as rhetorical-pedagogical expressions of Epictetus’ intellectualism. I will mainly focus on a series of problematic passages that have been discussed by several commentators concerning the concept of proairesis, and I will suggest that those passages are best interpreted as rhetorical or, better, pedagogical expressions of Epictetus’ strictly intellectualist approach to the psychology of action. The interpretation I will propose does away with the need to resort to certain interpretations of those passages that threaten to obscure the otherwise clear picture of human action offered by Epictetus’ intellectualism concerning the psychology of action.